Analisis Metode Pencatatan dan Penilaian Persediaan Barang Dagang pada Umkm Menurut Sak EMKM (Studi Kasus pada Toko Bangunan Pintu Rizky Mandiri) - Mawaddatussurur, Dewita; Lilis Lasmini; Trias Arimurti (BUDGETING : Journal of Business, Management and Accounting, 2025)
The Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) is an accounting framework specifically designed to meet existing needs. With the primary goal of enhancing financial transparency and accountability for medium-sized businesses, SAK EMKM is expected to contribute to sustainable economic growth. This study aims to identify and analyze inventory recording and valuation methods at Toko Bangunan Pintu Rizki Mandiri. The research employed a qualitative descriptive method. The analysis results indicate that the store has not yet fully complied with SAK EMKM.   Keywords: Inventory Recording and Valuation, SAK EMKM, Small and Medium Enterprises (SMEs)